The Influence of Hadrah Arts and Emotional Intelligence Towards the Students Social Skills at MTS Nurusshibyan - Fatimah, Siti (UI Scholars Hub, 2025)
This study aims to determine the effect of hadrah activities and emotional intelligence on the social skills of students at Madrasah Tsanawiyah Nurusshibyan, Singkawang City. This research uses a quantitative research method with the use of questionnaires as a data collection tool. The subjects of this study were students at Madrasah Tsanawiyah Nurusshibyan in Singkawang City totaling 181 people with the following characteristics: MTs students, grades VII-IX, 101 female respondents and 80 male respondents. The sample determination used the Slovin formula with a Margin of Error of 5%. The results of the study are as follows: (1) Social skills at Madrasah Tsanawiyah Nurusshibyan, Singkawang City are classified as very good with a score of 50.23%; (2) Hadrah activities at Madrasah Tsanawiyah Nurusshibyan, Singkawang City are classified as good with a score of 55.15%; (3) Emotional intelligence in Madrasah Tsanawiyah Nurusshibyan Singkawang City is classified as very good with a score of 39.82%. The conclusion of this study is that social skills are influenced by the variables of hadrah activities and emotional intelligence by 23.21% simultaneously, while the other 76.79% are influenced by other variables. The implications of this study can be used as input in improving social skills in Madrasah Tsanawiyah Nurusshibyan Singkawang City.